The Arabic dialect of the Rwala tribe, based on the ethnographic records of Alois Musil - O'Hara, J (2019)
This thesis presents a linguistic description of the dialect of the Rwala tribe of northern Arabia as presented in Alois Musil’s (1928) ethnographical work 'The manners and customs of the Rwala bedouins'. A systematic presentation of the phonology and morphology is given, which compares the grammar of the language as Musil recorded it with other sources of the Rwala dialect, and with sources of north-Arabian dialects more broadly, in order to assess the fidelity of Musil’s transcriptions. A complete glossary of Musil’s work has been compiled according to the grammar as set out in the rest of the thesis.